Catégorisation des trajectoires et méconnaissance institutionnelle - Bertrand Geay (Les éditions de la Maison des sciences de l'Homme, 2003)
In order to understand the ways in which the attitudes towards young dropouts are built, one can first look at objective data concerning school trajectories and second, point out the main features of their curriculum viewed by experts on the subject and last, see how the scientific world has recently taken hold of the problem. This analysis is based on literature recently imported in France on "deschooling", and on a large scale survey which took place in Picardie, Poitou-Charentes and in the region of Paris. It shows how the social background, the school conditions which lead to such trajectories are oversha-dowed and the professional and scientific logics which may lead to such a reification of the phenomenon.